Gestión financiera y tributaria en empresas del sector belleza, ciudad de Iquitos, 2021 - Vásquez Erazo, Raisa Nicole (2022)
Financial management is key to the success of companies today, considering that the proper use of resources allows maximizing business benefits, leading to the success or failure of the business, while compliance with tax obligations contributes to significant financial and business health, since it allows balance and avoids costs due to the imposition of fines, the objective of the research was to analyze the financial and tax management in companies in the beauty sector of the city of Iquitos in the year 2021, for which a focus was given quantitative with a type of descriptive study and non-experimental cross-sectional design, considering a study population of 60 companies, the data was obtained by applying a data collection instrument with 30 items which was subjected to a reliability test. with a result of 0.959 in Cronbach's Alpha, was identified that the ma Most companies implement financial management practices such as planning, control and analysis, in relation to tax management Most of the participants consider that they have tax knowledge, frequently implement tax planning actions and consider that they comply with their obligations tax, concluding that the financial and tax aspect is considered acceptable and that the level of importance shown is high, however, there is a small number of companies that do not practice financial or tax activities and do not recognize their importance.